Geomechanical Model Proposal for Optimizing Ramp Design in an Underground Gold Mine at Yanaquihua, 2024 - Diaz Chiguay, Luis Alejandro Patrick; Huamani Montalvo, Frank Jose; Macedo Franco, Luisa Diomira; Velarde Lam, Diego Manuel (LACCEI, 2025)
This research project develops a geomechanical model focused on optimizing the design of ramps in underground gold mines, specifically in the Yanaquihua mining operation, Peru. The importance of understanding the geological and geomechanical properties of the rock mass is highlighted to ensure stability and safety in mining operations. The research responds to the need to improve support and haulage systems, which are key components to maintain operability, safety and efficiency in underground mines. Through an exhaustive geomechanical analysis, which includes the evaluation of critical parameters such as Rock Mass Index (RMR) and Rock Quality Designation (RQD), which allowed the development of an adequate support system and improve operational efficiency. This model seeks to reinforce the stability of the excavations, minimize operational risks and allow greater load capacity and safe movement of equipment. One of the key findings was the competitiveness of the rock mass, which led to the consideration of increasing the dimensions of the ramp, an option that had not been previously considered, improving the transport of the extracted material, contributing to a safer and more productive mining operation. It is concluded that the implementation of an optimized geomechanical model not only improves structural stability, but also provides a safer working environment, reducing risks for personnel. Furthermore, it is suggested that this model can be replicated in other small-scale mining operations, contributing to the sustainability and efficiency of underground activities.